Can Students’ Computer Programming Learning Motivation and Effectiveness Be Enhanced by Learning Python Language? A Multi-Group Analysis - Ling, Hsiao-Chi; Hsiao, Kuo-Lun; Hsu, Wen-Chiao (Frontiers in Psychology, 2021)
Python language has become the most popular computer language recently. Python is widely adopted in computer courses. However, in the colleges and universities, the effects of Python language on the students' learning performance, motivations, computer programming self-efficacy, and maladaptive cognition are still not widely examined. The main object of this study is to explore the effects on the students' programming learning. The junior students of two classes in a college are the research participants. One class was taught Java language, and the other class was taught Python language. The learning performance, motivations, and maladaptive cognition in the two classes were compared to evaluate the differences. The results showed that the motivations, computer programming self-efficacy, and maladaptive cognition on the learning performance were significant in the Python class. The results and findings of this study can be used in Python course arrangement and development.